Mortality causes in children 1-59 months in iran. - M Rahbar; M Ahmadi; Hr Lornejad; A Habibelahi; T Sanaei-Shoar; Ar Mesdeaghinia (Tehran University of Medical Sciences, 2013)
Mortality rate indicator for children under 5 years old is one of the important indicators in countries' development. Identifying the most common causes of mortality is one of the most important attempts to reduce mortality in children less than 5 years. The purpose of this study was to identify distribution of the mortality causes in Iranian children less than 5 years.This cross-sectional study has been carried out based on the results of data from the Child Mortality Surveillance System since 2007 to 2008. To determine the causes of death questionnaires have been designed which include personal data of the deceased child, medical history, and information on procedures at the time of hospitalization or death.Of 5926 deaths on children under 5 years which the questionnaires were filled out, 63.2% were postneonatal deaths (1-11 month). Totally 60% of mortalities occurred in the rural areas and 52% of them had been among boys. The most common causes of mortality were the congenital and chromosomal abnormalities with 23.4%. The most incidences among diseases were respiratory system diseases.Carrying out more epidemiologic studies, providing health programs to control and prevent diseases with high incidences and delivering more specialized health facilities and services could be the proper strategies to reduce under 5 mortality rates in Iran.